ANALISIS EFEKTIVITAS PENGGUNAAN GOOGLE FORM DALAM DIGITALISASI PELAYANAN SURAT PENGANTAR DI KANTOR DESA BERGOLO - Wahid, Ahmad; Susanti, Anis (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the effectiveness of using Google Forms in managing the introductory letter service at Bergolo Village Office, Ngawen District, Blora Regency, using a qualitative descriptive approach. A total of 30 respondents, consisting of village officials and service users, participated. The assessment based on the Technology Acceptance Model (TAM) indicators showed that 93% of respondents perceived Google Forms as useful (perceived usefulness), 90% found it easy to use (perceived ease of use), 91% had a positive attitude toward the system (attitude toward use), and 92% intended to continue using it (behavioral intention). The implementation of Google Forms improved service efficiency, reduced paper usage, increased data accuracy, and facilitated real-time monitoring. The main challenges were limited internet access and low digital literacy among elderly residents. Therefore, training and infrastructure improvements are necessary to optimize the system. Overall, the use of Google Forms based on TAM proves to be an effective model for modernizing village administrative services that are fast, transparent, and easily accessible to the community.